Strengthening Global Health Research - Lars L. Gustafsson (Taylor & Francis Group, 2023)
Global Health is a young discipline with equity of health and services as its core value. The discipline has a tradition of close links between practice and research in line with the 'Health for All' declaration launched by the World Health Organization (WHO) in 1978. The multitude of existential health crises facing mankind require a research agenda in line with Global Health Research core values and methods, such as transdisciplinary collaboration, long time series of population-based observations and multifaceted interventions. Knowledge gaps cover climate effects on health and mechanisms for global spread and control of antibiotic resistance across species. Such health threats are preferably studied at Health and Demographic Surveillance Sites, a scientific infrastructure for Global Health Research in Africa and Asia, that gains to expand and monitor climate parameters and include sites in the northern hemisphere. Global Health Scientists together with science societies can ensure long-term funding of a global network of population-based health-climate sites. Global Health Scientists and scientific journals should jointly provide data and evidence on global health to governance bodies on regional, national and global levels, in particular to WHO and United Nations in charge of the programme with Sustainable Development Goals.